KOMUNIKASI DALAM IMPLEMENTASI KEBIJAKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DILAKUKAN DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BOLAANG MONGONDOW - POSANGI, HAFIS ALDANI; LENGKONG, FLORENCE; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to study how communication in the implementation of populationadministration policies in the Population and Civil Registry Office of North Bolaang MongondowRegency. The study uses descriptive qualitative method. Policy communication is seen from threeimportant aspects of public policy communication, namely transmission, clarity, and consistency.Research informants are the head of the department, heads of departments, staff / executors, sub-districtheads, village heads and the approved community. Data collection uses interviews, while the analysistechnique used is an interactive model analysis from Miles and Hubernann. Based on the researchresults, conclusions can be drawn: (1) Information dissemination and information on populationadministration policies are given effectively to the sub-district and village / village governments and to thecommunity. (2) Population administration administration policy is clearly communicated to all partiesboth to the sub-district and village / village government and to the community. (3) Information orexplanation regarding population administration administrative policies submitted by officers inaccordance with what has been determined or stated in the policy, both according to administrativerequirements for each type of service, service procedures, service administration costs, service delivery,and matters the other.Keywords: Policy communication, Population administration services.